Constitutionalism and democratic legitimacy - Contribution of legal policy - Santos, Adelcio Machado dos (Seven Editora, 2023)
The Science of Law can be defined as knowledge, methodically coordinated, which results from the ordered study of legal norms in order to apprehend their objective meaning and to build the legal system, as well as to discover its historical and social roots. The word right comes from the Latin directum, which corresponds to the idea of rule, direction, without deviation. In a very comprehensive way, it can be said that the word right has three meanings, that is, the rule of mandatory conduct; the system of legal knowledge and the faculty or powers that a person has or may have. On the other hand, it can be interpreted as the coercively applicable norm; and, on the other hand, it hosts the most varied contents. This shows the fundamental problem, which gave rise to the various currents of legal thought, all claiming to have found the foundation of Law. This article analyzes the contribution of Legal Policy. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-111